Temporal and Spatial eDNA Analysis of Fish Assemblages in Postindustrial, Urban Coastal Habitats - Alice Cunnington; Erika Neave; Peter Shum; Rupert Collins; Stefano Mariani (Environmental DNA)
ABSTRACT Urban coastal habitats experience substantial disturbances due to their proximity to human settlements and activities. Yet, despite the negative impact of urbanization on coastal environments, industrial structures can also provide artificial habitats. These are often easily accessible to regular surveys, including water sampling for environmental DNA (eDNA) analysis, an emerging and powerful tool for monitoring biodiversity in aquatic ecosystems. In this study, we utilized eDNA metabarcoding to investigate temporal and spatial trends in fish assemblages within urban coastal habitats between the Dee and Mersey estuaries (United Kingdom), historically one of the most anthropogenically impacted postindustrial coasts in the world. Over a 12‐month period, we conducted nine water sampling trips at two locations: the Albert Docks in central Liverpool, and the Marine Lake in West Kirby. Illumina sequencing was used to analyze PCR amplicons generated using the fish‐targeted Tele02‐12S metabarcoding region. We found significant changes in fish community composition across the different months. Fish communities also significantly differed between the two sites, with the patterns of temporal changes varying substantially between them. Seasonal appearances/disappearances of specific taxa (e.g., European eel, sand smelt, flounder, and herring) shed light on important ecological and behavioral processes that may have management implications. Results also corroborate previous findings on the importance of “molecular bycatch” (nontarget sequences) in expanding our understanding of the anthropogenic influences on the natural environment. Overall, our findings emphasize the value of eDNA monitoring as a noninvasive, affordable, and sensitive approach for routine monitoring of temporal trends in fish assemblages, facilitating the stewardship of resilient urban coastal zones, and recognizing interventions that could increase biodiversity.